HAMBATAN SETORAN TAHFIDZ MAHASISWA PADA MASA PANDEMI DI INSTITUT ILMU AL-QUR’AN JAKARTA - Farihin, Prianka Ayu (Program Studi Ilmu Al-Qur'an dan Tafsir, Universitas Islam Negeri Datokarama Palu, 2022)
Since mid-2020, it started with the entry of the Covid-19 virus into Indonesia, which reportedly came from China and resulted in a very fast transmission process. This also affects new habits in the field of education. According to data from the United Nations Educational, Scientific and Cultural Organization (UNESCO), there are at least 290.5 million students worldwide whose learning activities are disrupted due to schools being closed. The impact of this pandemic has also resulted in changes to the learning system at the Jakarta Institute of Al-Qur'an Science (IIQ), including the student tahfizH deposit activity. Therefore, the campus must look for new learning alternatives, namely by implementing online distance learning. This application certainly has its own advantages and challenges. Apart from this online learning can provide flexibility of time for students and instructors, researchers want to know more about the implementation and obstacles of the online tahfidz deposit activity.